The human complement receptor type 2 (CR2)/CR1 fusion protein TT32, a novel targeted inhibitor of the classical and alternative pathway C3 convertases, prevents arthritis in active immunization and passive transfer mouse models. (January 2019) - Fridkis-Hareli, Masha; Storek, Michael; Or, Eran; Altman, Richard; Katti, Suresh; Sun, Fang; Peng, Tao; Hunter, Jeff; Johnson, Krista; Wang, Yi; Lundberg, Ante S.; Mehta, Gaurav; et al.
Highlights: TT32 is a CR2/CR1, 120 kDa fusion protein that possesses potent C3 and C5 classical and alternative pathway convertase inhibitory activity capable of inhibiting all three pathways of complement. TT32 is new and distinct from TT30, which also binds to C3d and iC3b through the CR2 domain, but is rather an AP pathway-specific inhibitor. TT32 ameliorated disease in both the CIA and CAIA mouse models of inflammatory arthritis. Abstract: Complement activation in human diseases is characterized by the local covalent deposition of the long-lived C3 fragments iC3b/C3dg/C3d. Previously, TT30, a complement alternative pathway (AP)-selective inhibitor, was designed as a fusion protein linking the first four short consensus repeats (SCRs) of human complement receptor type 2 (CR2) with the first five SCRs of human factor H (fH). TT30 acts by utilizing CR2 SCR1–4 to bind the initially formed iC3b/C3dg/C3d fragments and delivering surface-targeted inhibition of AP C3 and C5 convertases through fH SCR 1-5. In order to combine classical (CP) and lectin (LP) pathway inhibitory abilities employing CR2-mediated targeting, TT32 was developed. TT32 is a CR2-CR1 fusion protein using the first ten SCRs of CR1, chosen because they contain both C3 and C5 convertase inhibitory activity through utilization of decay-acceleration and cofactor activity for both AP and CP. In Wieslab assays, TT32 showed potent inhibition of the CP and AP with IC50 of 11 and 46 nM, respectively. The TT32 inhibitory activity is partially blocked with a molar excess of a competing anti-CR2 mAb, thus demonstrating the importance of the CR2 targeting. TT32 was studied in the type II (CII) collagen-induced arthritis (CIA), an active immunization model, and the CII antibody-induced arthritis (CAIA) passive transfer model. In CIA, injection of 2.0 mg TT32 at day 21 and 28 post disease induction, but not untargeted CR1 alone, resulted in a 51.5% decrease in clinical disease activity (CDA). In CAIA, treatment with TT32 resulted in a 47.4% decrease in CDA. Therefore, a complement inhibitor that targets both the AP and CP/LP C3/C5 convertases was shown to limit complement-mediated tissue damage and inflammation in disease models in which all three complement activation pathways are implicated.